Open-Source Software in Medical Imaging: Case-Based Study with Interdisciplinary Innovative Product Design: Odprtokodna programska oprema za medicinske slike: študija primera na podlagi interdisciplinarne inovativne zasnove izdelka - Harih, Gregor; Čretnik, Andrej (Acta Medico-Biotechnica, 2021)
Purpose: Recently, comprehensive open-source software (OSS) solutions for medical images have been developed. They offer powerful tools for the management, visualization, storage and analysis of images. The purpose of the present study was to present the features and use of OSS in comparison with commercial software solutions when evaluating medical images.Methods: A case study of the development of a tool handle of optimal size and shape using the free OSS “3D Slicer” is presented. Many authors recommend cylindrical-shaped handles to increase comfort, performance and to avoid cumulative trauma, but none have considered the optimal shape of the handle. Hence, we derived a method for obtainingan optimally shaped tool handle based on the power grip hand posture and non-deformed soft tissue. During magnetic resonance imaging (MRI), an outer hand mold was used to maintain the optimal hand posture. 3D Slicer was used for segmentation and 3D reconstruction of MRI. A three-dimensional (3D) hand model was exported to a commercial program for computer-aided design for the optimal tool handle.Results: Measurements of the diameters on 3D reconstruction showed that the position of fingers wasere withheld within small deviations, which maximized maximum finger force exertion. An optimally shaped handle this way provided 25% higher contact area compared with the optimal cylindrical handle. It therefore reduced contact pressure, increased performance and comfort and could probably prevent disorders due to cumulative trauma.Conclusion: This case study supported the use of OSS for medical imaging as a powerful and (mostly) free tool comparable with (usually expensive) commercial solutions.
Keywords: tool handle; open source; ergonomics; segmentation; medical imaging; 3D hand model